Integration of Knowledge of Solar Thermal and Solar PV Technologies in Physics Education for Enhancing Skill Development - Sengar, Namrata (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The world is making a transition towards clean energy choices and for this solar energy is a promising option which is growing at a tremendous rate. In order to combat the global warming and climate change, many countries especially India has set ambitious targets for next 20-30 years focusing on increasing the use of solar energy for various applications. As solar PV and thermal technologies are growing and penetrating in the everyday life applications, it becomes important to make these a part of physics education. Understanding of these technologies by a physics student will offer opportunities for skill development, innovation and research. Department of Pure and Applied Physics, University of Kota offers courses and special paper related to Energy Studies and more specifically Solar Energy. The present work discusses the integration of the knowledge of solar energy technologies in the physics curriculum both in theory and experiments. Further the experience of the Higher Education Partnership Project on Solar Energy Materials and Technologies awarded to the University of Kota by the Royal Academy of Engineering, UK and FICCI, India is also shared. The studies related to solar energy applications enhanced the knowledge of heat transfer, thermal physics, electrical and electronics which in turn results in skill development and opportunities for innovation